THE EFFECTIVENESS OF HEAT TRANSFER PRACTICUM WITH CARD SORT MEDIA TO STUDENTS’ CRITICAL THINKING ABILITY - Khusniati, Miranita; Hasasiyah, Siti Hardiyanti; Parmin, Parmin; Kurniyawan, Deni (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
This research aims to know the effectiveness of media cards (Card Sort)-based experiments to improve students’ critical thinking skills. The design of this research is the control group pretest posttest design. Samples taken in pusposive sampling and obtained Class VII F as a Class VII and class B experiments as a control class. This research data is the data value of the posttest and observation data of critical thinking skills of students. The results of this study indicate that the average value of experimental class posttest is 79.18 66.25 control and class. The t-test analysis results 4.62 whereas t table 1.67. Based on observation, analysis results the average rating on the class control at each meeting of 36% (not critical), 53% (quite critical), 66% (critical) while the average in class experiments at each meeting is 52% (quite critical), 69% (critical).